2012
DOI: 10.1080/13825585.2011.628378
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and neurophysiological effects of strengthening exercise for early dementia: A pilot study

Abstract: Research demonstrates a positive effect of aerobic exercise on cognitive functioning in older adults. Unfortunately, aerobic exercise is often contraindicated for older adults due to cardiovascular and functional limitations. Low-intensity strengthening exercise may offer a practical alternative, but the neuropsychological benefits and potential neurophysiological mechanisms are less well understood. The current study evaluated the effects of a 10-week strengthening exercise intervention on cognitive functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Although this relatively short-duration RT program did not produce improvements in executive function, the authors speculated that the changes in neurophysiological mechanisms might occur quicker than neuropsychological measures of executive function in response to exercise. Taken together, these observations (3,10,36,71) suggest that aspects of cognitive functioning differ in how they may be affected by RT on different time scales and in response to different training intensities and modalities in older adults. Furthermore the cognitive benefits provided through RT may be selective and sex specific; specifically, improved memory and verbal concept formation may be more pronounced in men (10,71), while improved executive function may be more likely to occur in women (3,36).…”
Section: Resistance Exercise Training and Cognitive Healthmentioning
confidence: 83%
See 1 more Smart Citation
“…Although this relatively short-duration RT program did not produce improvements in executive function, the authors speculated that the changes in neurophysiological mechanisms might occur quicker than neuropsychological measures of executive function in response to exercise. Taken together, these observations (3,10,36,71) suggest that aspects of cognitive functioning differ in how they may be affected by RT on different time scales and in response to different training intensities and modalities in older adults. Furthermore the cognitive benefits provided through RT may be selective and sex specific; specifically, improved memory and verbal concept formation may be more pronounced in men (10,71), while improved executive function may be more likely to occur in women (3,36).…”
Section: Resistance Exercise Training and Cognitive Healthmentioning
confidence: 83%
“…Improvements in executive function were specific for verbal measures of neuropsychological performance rather than global executive functioning, suggesting that certain aspects of executive function may be affected differentially by exercise modality. Yerokhin et al (71) furthered this notion, observing that improved verbal memory (Fuld Object Memory Evaluation) was correlated with improvements in resting frontal lobe neurophysiology (electroencephalographic reduction in N200A and increase in delta asymmetry) following a 10-wk progressive, low-intensity RT program in older adults with MCI as determined by a resident physician. Although this relatively short-duration RT program did not produce improvements in executive function, the authors speculated that the changes in neurophysiological mechanisms might occur quicker than neuropsychological measures of executive function in response to exercise.…”
Section: Resistance Exercise Training and Cognitive Healthmentioning
confidence: 97%
“…Based on these, exercise intervention and cognitive training programs have been used to challenge older adults. Interventions for increasing physical activity improved cognition in relatively healthy older adults,59,60 and in patients with early dementia 61. Of note, a six-month aerobic fitness training demonstrated increased brain volumes and functional plasticity among in patients with early dementia and otherwise healthy subjects 59,60,62.…”
Section: Target Populations and Topicsmentioning
confidence: 90%
“…Yerokhin et al demonstrated that 10 weeks of resistance training increased the cognitive efficiency of patients with early dementia. 14 Cassilhas et al reported improvements in cognitive function, mood profile, anxiety, and quality of life among older adults after 6 months of resistance training. 15,16 In addition to resistance training, previous studies of patients with schizophrenia have used a combination of aerobic and resistance exercises in the same session, which is known as concurrent exercise.…”
Section: Introductionmentioning
confidence: 99%